Formulation Characterization and Evaluation of Meloxicam Nanoemulgel to be Used Topically - Hayder Kadhim Drais; Ahmad A. Hussein (College of Pharmacy University of Baghdad, 2017)
Meloxicam is a non-steroidal anti-inflammatory drug. It is practically insoluble in water. It is associated with gastrointestinal side effects at high doses on long  term treatment. The aim of this investigation to formulate and evaluate gellified nanoemulsion of meloxicam as a topical dosage form to enhance meloxicam therapeutic activity and reduce systemic side effect. The pseudo ternary phase diagrams were made, including  the oil mixture which is composed of almond oil and peppermint oil at a ratio (1:2), variable surfactant mixture (S mix) which are tween 80 and ethanol at ratios of (1:1, 2:1, 3:1, and 4:1) and double distilled water. Slow dripping of double distilled water to the combination  of the oil mixture and Smix was performed to get nanoemulsion. The pseudo ternary phase diagram that has a greater nanoemulsifying area was contained  Smix ratio (3:1) from which seven formulas of nanoemulsion (NE1-NE7) were taken for characterization of prepared nanoemulsions and to prepare nanoemulgel formulas (NF1-NF7). The seven nanoemulgel formulas were subjected to various evaluations. NF1 was the selected formula and investigated for its stability and morphology. Atomic force microscopy (AFM) indicated that the optimized formula (NF1) was nanosized particle nearly spherical in shape and smooth surface globules, this indicates  stability of optimized nanoemulgel (NF1). It can be concluded that the selected formula (NF1) is an effective alternative for the topical delivery of meloxicam. Keywords: Meloxicam, Nanoemulgel, Arthritis.